PENERAPAN MONITORING TERHADAP PENCATATAN PEMBIAYAAN & PENGIKATAN NOTARIS PADA PT BPR BKK JATENG (PERSERODA) KC MAGELANG - Putri, Vina Aprilia; Utami, Martiana Riawati (Journal Accounting International Mount Hope, 2025)
PT BPR BKK Jateng (Perseroda) KC Magelang is a microfinance institution that is ready to serve the needs of the community for credit and savings. This study aims to analyze the implementation of monitoring of financing recording & notary binding at PT BPR BKK Jateng (Perseroda) KC Magelang. Effective monitoring of the financing recording and notary binding process is very important to ensure security and compliance in banking operations. The research used is a qualitative method with a case study approach, which includes in-depth interviews with related parties, direct observation, and document analysis. The results of this study provide recommendations for improving the effectiveness of monitoring, including the use of more advanced information technology.